Sistem Informasi Alumni Studi Kasus UIN Alauddin Makassar - Muin, Asrul Azhari; Rahman, Rahman; Andi Maryam, Andi Anisa (Jurnal INSYPRO (Information System and Processing), 2025)
Kata Kunci: Informasi, Tracer study, Website. Abstract - The development of information and communication technology is something that cannot be denied today, technological advances are in line with existing scientific advances that have provided a lot of convenience in carrying out various activities. Alumni tracer or often also called Tracer Study is a way used to find out the condition of alumni, monitor alumni, and be able to find out how alumni work whether it is in accordance with the competencies that alumni have. Tracer study is also used as a material for evaluating educational outcomes, because the study program examines the transition between education while at university and the professional world or in the world of work. Tracer study plays an important role in meeting the needs of an educational institution, this tracer study is a means used to obtain graduate data from alumni through website development. Recording Alumni information is no longer limited to alumni printed books that only record limited information and focus on numbers Keywords: Information, Tracer study, Website